Regional Rules and the National Legal System - Landa Arroyo, César (1985)
The paper studies the history of failed attempts at decentralization in Peru, from its independence until the 1979 Constitution. It points out that, throughout this period, various proposals such as Departmental Boards and Regional Councils were created with the aim of combating centralism, but all of them proved ineffective. It also delves into the concept of legal system, emphasizing that it is not only a collection of laws, but a cohesive system of interrelated norms. Based on this, the author analyzes the creation of norms at the regional level and their relationship with the national normative framework, suggesting an adequate hierarchy and coordination between both levels to achieve effective decentralization, which could help to find fair and coherent solutions to social and normative conflicts. Finally, the author emphasizes the relevance of certain principles, such as constitutionality, relative regulatory autonomy, legality and competence. In particular, the principle of relative normative autonomy is highlighted, as it is aligned with the organic model of government enshrined in the 1979 Constitution, and also, in the author's opinion, challenges the classical idea of prevalence of the norm issued by the highest hierarchical body.